Continuous wave milipulse yellow laser treatment for perifoveal exudative vascular anomalous complex-like lesion: A case report. Issue 1 (January 2022) - Henriques, José; Pinto, Filomena; Rosa, Paulo Caldeira; Medeiros, Marco Dutra; Reis Cabral, Diogo; Henriques, Susana; Nascimento, João
Introduction: Perifoveal exudative vascular anomalous complex (PEVAC) is an underdiagnosed macular entity. A striking feature of this entity is the unresponsiveness to anti-VEGF treatment. Continuous wave milipulse yellow laser 577 nm (CWMYL-577) has a high absorption peak for oxyhaemoglobin, which allows for low power density use. Purpose: To report a case of a PEVAC-like lesion unresponsive to anti-VEGF and corticosteroids, successfully treated with a single session of minimally invasive focal laser, using CWMYL-577. Methods: A diabetic patient with a symptomatic PEVAC-like lesion in the right eye, presented with decreased vision (20/100) and cystoid edema that had persisted for the last 18 months, despite multiple intraocular injections of anti-VEGF and long acting corticosteroids. Three spots of low power density CWMYL-577 (100 mW, 25 ms and 100 µm, using lens with no amplification factor) over the lesion were successfully performed in one laser session. One month and three months after the laser procedure, a gradual decrease of edema and lipid exudates was observed and at a 6-month follow-up, the retina had recovered its normal anatomy with visual acuity of 20/20 that have persisted for 4 years after treatment. Conclusions: Minimal invasive focal laser using the CWMYL-577 can be considered an effective therapeutic strategy for symptomatic nonresponding PEVAC-like lesion in patients with DM without DR.